EVALUASI INTERNAL PROGRAM STUDI MENGGUNAKAN METODE NAÃVE BAYES CLASSIFIER (NBC) - Yoseph Pius Kurniawan Kelen (SAINTEKBU, 2017)
ABSTRACTThe Development of department and study program can not be seperated by its internal factors which is influenced number of candidate of students it self direct or indirectly.Â  In this case we need a method to know the condition in each internal variables that will be evaluated in the department itself.NBC method is kind of simple Bayesian Network that comes with assume statement that all features are similar one with another. Nbc shows the great work completely in accuracy and failed classification level. NBC could predict some assume for prediction needs.This research generally made to use for evaluating department and study program internarly by clasifying some variables which can influence to know about the condition of the deprtment and the study program itself. This is also one 8f best strategy to develope number of new cndidte of students and this method will shows about the study program to the new candidate of students.Key words : NBC, study program evaluating.Â